2014
DOI: 10.1139/cjm-2013-0492
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of metal ions and isothiazolones in inhibiting Enterobacter cloacae BF-17 biofilm formation

Abstract: Enterobacter cloacae is a nosocomial pathogen. The E. cloacae strain BF-17, with a high capacity for biofilm formation, was screened and identified from industrially contaminated samples, carried out in our laboratory. To develop an efficient strategy to deal with biofilms, we investigated the effects of metal ions, including Na⁺, K⁺, Ca⁺, Mg⁺, Cu⁺, and Mn⁺, and 3 isothiazolones, on elimination of E. cloacae BF-17 biofilm formation by using a 0.1% crystal violet staining method. The results revealed that highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 30 publications
1
14
0
3
Order By: Relevance
“…strains during the processing of milk formulations (Somerton et al, 2013 ). Another recent study has showed that biofilm formation decreased with increasing concentration of Mg 2+ in Enterobacter cloacae (Zhou et al, 2014 ). Although recent studies have shown that magnesium might have diverse effects on biofilms, the effect of Mg 2+ ions on biofilm formation by sporulation Bacillus species remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…strains during the processing of milk formulations (Somerton et al, 2013 ). Another recent study has showed that biofilm formation decreased with increasing concentration of Mg 2+ in Enterobacter cloacae (Zhou et al, 2014 ). Although recent studies have shown that magnesium might have diverse effects on biofilms, the effect of Mg 2+ ions on biofilm formation by sporulation Bacillus species remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Ca supplementation has been shown to promote biofilm formation in Pseudomonas aeruginosa (Sarkisova et al ., ), Pseudoalteromonas sp. (Patrauchan et al ., ), Sinorhizobium meliloti (Rinaudi et al ., ), Xylella fastidiosa (Cruz et al ., ), Enterobacter cloacae (Zhou et al ., ), Aeromonas hydrophila (Das et al ., ), and Enterococcus faecalis (Das et al ., ), while it suppresses biofilm formation in Vibrio cholerae (Bilecen and Yildiz, ) and Staphylococcus aureus (Shukla and Rao, ). While Ca, as a divalent cation, can function to neutralize cell surface charges to facilitate binding and adhesion (Leite et al ., ; Williams, ), growing evidence suggests a role for Ca that is regulatory and not just physical/structural (Shemarova and Nesterov, ; Cruz et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Биоплёнки защищают бактерии от воздействия внешних физико-химических факторов: антибиотиков, ультрафиолетового облучения, механического воздействия и т. п. [10]. Удалить и инактивировать развитые и зрелые биоплёнки достаточно трудно [10], что приводит к нежелательным проблемам, особенно в медицине и промышленности.…”
unclassified
“…Удалить и инактивировать развитые и зрелые биоплёнки достаточно трудно [10], что приводит к нежелательным проблемам, особенно в медицине и промышленности. Возможность контроля образования биоплёнокэто междисциплинарная научная задача, изучаемая давно и активно [10]. Обнаружено [11] Mg, магнитный 25 Mg и природный изотоп магния (ФГУП "Электрохимприбор", Россия) [8].…”
unclassified
See 1 more Smart Citation